Conceptualizing the Influence of Souvenir Image and Place Identity on Souvenir Repurchasing Intentions - Chen, Dong; Yaacob, Husaini Bin (South Asian Journal of Social Sciences and Humanities, 2024)
The local traditions, including arts and crafts, are considered as the important things by which the tourism industry can be attracted by a particular country. The souvenirs are the best tool to tell friends or family about your concern towards them during traveling. Chinese ceramics are considered classic souvenirs to purchase while traveling because the ceramic products have been utilized by the residents for many years. Chinese people have a very significant and firm attachment to their native products they call them souvenirs. The purchase of souvenirs is an integral part of a country’s tourism sector. Therefore, this conceptual paper explores the role of souvenir image, and place identity in boosting the re-purchase intentions of Chinese tourism industry employees for souvenir products. The researcher has reviewed the existing literature to propose a framework to investigate the determinants of the re-purchase intentions for souvenir products. Thus, the study contributed to the existing body of literature on the determinants of re purchase intentions. The proposed research framework has made a significant addition to the literature.